A robust, high-flux source of laser-cooled ytterbium atoms. (9th February 2021) - Wodey, E; Rengelink, R J; Meiners, C; Rasel, E M; Schlippert, D
Abstract: We present a high-flux source of cold ytterbium atoms that is robust, lightweight and low-maintenance. Our apparatus delivers 1 × 10 9 atoms s −1 into a 3D magneto-optical trap without requiring water cooling or high current power supplies. We achieve this by employing a Zeeman slower and a 2D magneto-optical trap fully based on permanent magnets in Halbach configurations. This strategy minimizes mechanical complexity, stray magnetic fields, and heat production while requiring little to no maintenance, making it applicable to both embedded systems that seek to minimize electrical power consumption, and large scale experiments to reduce the complexity of their subsystems.